Transit Oriented Development Concept for Responsive Pedestrian on Pandanaran Street, Semarang City - Mila Karmilah; Rachmat Mudiyono; Safira S (Universitas Islam Sultan Agung, 2025)
The concept of Transit Oriented Development (TOD) entails city planning for sustainable urban development, through a system, that aims to reduce the use of private vehicles and increase the interest in walking and transit areas utilization. Jalan Pandanaran is one of the supporting roads located in Simpang Lima area, which is crowded with offices, trade, and service centers. This area has the potential of becoming a regional center or Central Business District (CBD), which implies that it is capable of having a sustainable transportation system through the TOD concept depending on the Regional Center it is being applied to. Therefore, this study aims to identify, analyze and determine the concept of planning the Transit Oriented Development (TOD) system in the Pedestrian Path of Jalan Pandanaran. The method used was rationalistic quantitative with scoring analysis techniques and pedestrian analysis. The result showed a feasibility assessment on the pedestrian path on Pandanaran Street, through the application of the concept of TOD system planning based on the responsiveness of pedestrian users on the path.